MicroRNA-9 and MicroRNA-326 Regulate Human Dopamine D2 Receptor Expression, and the MicroRNA-mediated Expression Regulation Is Altered by a Genetic Variant - Shi, Sandra (American Society for Biochemistry and Molecular Biology, 2014)
The human dopamine receptor D2 (DRD2) has been implicated in the pathophysiology of schizophrenia and other neuropsychiatric disorders. Most antipsychotic drugs influence dopaminergic transmission through blocking dopamine receptors, primarily DRD2. We report here the post-transcriptional regulation of DRD2 expression by two brain-expressed microRNAs (miRs), miR-326 and miR-9, in an ex vivo mode, and show the relevance of miR-mediated DRD2 expression regulation in human dopaminergic neurons and in developing human brains. Both miRs targeted the 3′-UTR (untranslated region) of DRD2 in NT2 (neuron-committed teratocarcinoma, which endogenously expresses DRD2) and CHO (Chinese hamster ovary) cell lines, decreasing luciferase activity measured by a luciferase reporter gene assay. miR-326 overexpression reduced DRD2 mRNA and DRD2 receptor synthesis. Both antisense miR-326 and antisense miR-9 increased DRD2 protein abundance, suggesting an endogenous repression of DRD2 expression by both miRs. Furthermore, a genetic variant (rs1130354) within the DRD2 3′-UTR miR-targeting site interferes with miR-326-mediated repression of DRD2 expression. Finally, co-expression analysis identified an inverse correlation of DRD2 expression with both miR-326 and miR-9 in differentiating dopaminergic neurons derived from human induced pluripotent stem cells (iPSCs) and in developing human brain regions implicated in schizophrenia. Our study provides empirical evidence suggesting that miR-326 and miR-9 may regulate dopaminergic signaling, and miR-326 and miR-9 may be considered as potential drug targets for the treatment of disorders involving abnormal DRD2 function, such as schizophrenia.